A shortened version of Raven's standard progressive matrices for children and adolescents. (27th May 2021) - Langener, Anna M.; Kramer, Anne‐Wil; van den Bos, Wouter; Huizenga, Hilde M.
Abstract : Numerous developmental studies assess general cognitive ability, not as the primary variable of interest, but rather as a background variable. Raven's Progressive Matrices is an easy to administer non‐verbal test that is widely used to measure general cognitive ability. However, the relatively long administration time (up to 45 min) is still a drawback for developmental studies as it often leaves little time to assess the primary variable of interest. Therefore, we used a machine learning approach – regularized regression in combination with cross‐validation – to develop a short 15‐item version. We did so for two age groups, namely 9 to 12 years and 13 to 16 years. The short versions predicted the scores on the standard full 60‐item versions to a very high degree r  = 0.89 (9–12 years) and r  = 0.93 (13–16 years). We, therefore, recommend using the short version to measure general cognitive ability as a background variable in developmental studies.